Inovasi Literasi Digital Untuk Penguatan Kewirausahaan Masyarakat RT 07 RW 02 Sawah Lebar Baru - Diwantoro, Dio Muhammad Yusub; Alvira. M, Dytha; Wulandari, Eka Setia; Santoso, Ervitro Augus; Pratiwi, Marshella Ayu; Sari, Venny (Universitas Dehasen Bengkulu, 2026)
This community service program, the KKN-T Digital Transformation Centres (DTC), was implemented in RT 07/RW 02 Sawah Lebar Baru Village, Bengkulu, to address the low level of digital literacy observed among local residents. The low literacy hindered their ability to utilize digital technology for productive economic activities, such as digital entrepreneurship and market targeting. The primary goal of the program was to enhance community knowledge and skills in digital literacy, specifically through training on Strategic Planning and Social Media Marketing to support technology-based entrepreneurship. Data were collected using observation and documentation, followed by qualitative analysis and validation via source and technique triangulation. The results showed a significant increase in the community's understanding regarding the effective use of digital platforms for product marketing, the importance of establishing a digital identity, and basic strategies for defining a target market. In conclusion, the DTC program successfully strengthened community digital capacity, providing a meaningful innovation to foster technology-based entrepreneurship in the area. The abstract should not contain any references or displayed equations.